INCREASING WILD PLANT SPECIES IN THE WESTERN DESERT DISTRICT OF IRAQ - O. M. Othman; A. M. A. AL-Kasiy; A. K. H. Al-Hazemawi; S. S. Shahatha; N. M. Abood; M. O. Mousa (مجلة الأنبار للعلوم الزراعية)
Based on the field surveys conducted in farms and prairies across the Western Desert District of Iraq from 1993 to 2023. which aimed to collect wild plant species and weeds; the study concluded to identify increasing wild plant species based on the geographic distribution and numerical density of species in general in this district. According to the ancient Iraqi Flora, and what was recorded during the current study, it resulted in the registration of 41 plant species rapidly spreading and increasing despite the environmental conditions variations and climate changes in the study area. These species were distributed among 13 plant families, with eight species distinguishing the Amaranthaceae and Asteraceae families by 19.5% each. The Brassicaceae and Poaceae families followed with five species each, with a percentage of 12.0%. The Fabaceae family included four species (9.7%), the Polygonaceae family had three species (7.3%), and the Malvaceae family only had two species (4.8%), while the rest of the six families were represented by a single species each, with a percentage of 2.4%. To ensure the modernity and acceptability of names in the scientific community, the study checked the names of all species to adopt those accepted globally, revealing nine species with synonymous scientific names. The information concerning all species was tabulated by mentioning the families they belong to, common names, plant habits, and duration. By referring back to the history of species in terms of their original environmental habitat or origin at the global level, it became clear that 36 species (87.8%) are native plant species in Iraq, while the remaining five species are non-native or introduced, accounting for 12.2%. This study considered that some of these species had exceeded the increase stage by invading agricultural fields and marginal lands to become invasive plants, represented by the Atriplex tatarica, Prosopis juliflora, and Solanum elaeagnifolium